Análise ultrassonográfica qualitativa e quantitativa da deglutição orofaríngea - Rocha, Simone Galli [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Among different technology used in oropharyngeal swallowing instrumental evaluation, considering cost-benefit ratio, tongue movement ultrasound stand out as a viable instrument to investigate orofacial functions. This study aims to describe and to define - both qualitatively and quantitatively - ultrasonographic parameters of oropharyngeal swallowing among healthy adults and to verify in what way the variables age group and consistency of food swallowed, as well as respective interactions, might interfere with ultrasonographic parameters. Ultrasonographic evaluations of swallowing were performed (using the DP 6600 portable ultrasound machine, a micro-convex probe connected to a PC, and a Stabilization Headset) in 100 people (divided into four groups: GI - 20 à 30 age, GII - 31 à 40 age, GIII - 41 à 50 age e GIV - 51 à 60 age), using liquids (both free volume and controlled swallow of 5 ml) and pudding-consistent food (controlled swallow of 5 ml). Tongue and hyoid bone movement, used as parameters to qualitative analysis, were adapted from a previous study. During the oropharyngeal swallowing, the presence of five markers was considered. The following parameters were regarded in the quantitative analysis: tongue movement propulsion duration during swallowing, and maximum displacement of the hyoid bone during swallowing peak. Considering qualitative ultrasonographic description, the results pointed that all volunteers presented the same standard tongue posture previous to food reception (phase 1) and containment (phase 2), regardless of food consistency and volume. During the bolus propulsion (phase 3), a wide intersubjective variety of wavelike movements was observed. Concerning maximum displacement of the hyoid bone (phase 4), the ultrasonographic image was analyzed having as reference a 45º angle, that is, for each kind of bolus, we considered displacements equal or under 45º, or above this. Generally, the angle ...

Dentre as diferentes tecnologias utilizadas para avaliação instrumental da deglutição orofaríngea, tendo como critério a relação custo/benefício, a ultrassonografia do movimento de língua se destaca como um instrumento viável para a investigação das funções orofaciais. O objetivo desse estudo é descrever e caracterizar qualitativamente e quantitativamente os parâmetros ultrassonográficos da deglutição orofaríngea em adultos saudáveis e verificar de que forma as variáveis faixa etária e consistência de alimento, bem como suas respectivas interações, interferem nos parâmetros ultrassonográficos. Foram realizadas avaliações ultrassonográficas da deglutição (com ultrassom portátil modelo DP 6600, transdutor micro-convexo acoplado a um computador, além do estabilizador de cabeça) de 100 indivíduos (divididos em 4 grupos: GI - 20 à 30 anos, GII - 31 à 40 anos, GIII - 41 à 50 anos e GIV - 51 à 60 anos) com a consistência líquida (volume livre e controlado de 5ml) e consistência pudim (volume controlado de 5ml). Os parâmetros para a análise qualitativa do movimento de língua e do osso hióide foram adaptados de um estudo prévio. Considerou-se a presença de cinco marcadores durante a deglutição orofaríngea. Para a análise quantitativa, foram observados os parâmetros: duração da propulsão do movimento de língua durante a deglutição e a distância do deslocamento máximo do osso hióide durante o pico da deglutição. Os resultados indicaram que, em relação à descrição ultrassonográfica qualitativa, todos os indivíduos, independente da consistência e volume do alimento apresentaram o mesmo padrão de postura de língua para a recepção do alimento (fase1) e apreensão do alimento (fase 2). Em relação à propulsão do bolo alimentar (fase 3), verificou-se uma grande variabilidade inter-sujeitos do movimento ondulatório da língua. Já para o pico máximo do deslocamento...
Keywords: Disturbios da deglutição - Diagnóstico; Deglutição; Ultrassonografia; Pesquisa quantitativa; Pesquisa qualitativa; Swallows